2021
DOI: 10.1155/2021/8545934
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis on Depression and Associated Factors among Adult HIV/AIDS-Positive Patients Attending ART Clinics of Ethiopia: 2021

Abstract: Introduction. Depression is the most common mental health problem in people living with the human immune virus. It ranges from 11% to 63% in low- and middle-income countries. Depression was high in people living with HIV/AIDS in developing countries, especially in the Ethiopian context. Even though depression has negative consequences on HIV-positive patients, the care given for depression in resource-limited countries like Ethiopia is below the standard in their HIV care programs. Method. International databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…It has been found that the 2-year mortality risk of those with depressive symptoms was 9.7%, higher than that of those without depressive symptoms among HIV-infected patients who inject drugs (17). Recent systematic reviews about the relationship between HIV and depressive symptoms showed that depressive symptoms were associated with gender, age, marital status, economic level, social support, HIV-1 RNA level, CD4 count, antiviral therapy, sexual transmission, opportunistic infections and social stigma among HIV/AIDS (18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the 2-year mortality risk of those with depressive symptoms was 9.7%, higher than that of those without depressive symptoms among HIV-infected patients who inject drugs (17). Recent systematic reviews about the relationship between HIV and depressive symptoms showed that depressive symptoms were associated with gender, age, marital status, economic level, social support, HIV-1 RNA level, CD4 count, antiviral therapy, sexual transmission, opportunistic infections and social stigma among HIV/AIDS (18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Confounding variables considered included age at last birthday [28,29], sex at birth (male, female, intersex, no response) [30,31] educational status (No formal education, primary level, secondary level and tertiary level) and self-report of depression [32,33]. Depression was assessed by asking respondents to indicate if they had experienced any of the 10 listed emotions during the pandemic, one of which was depression.…”
Section: Main Textmentioning
confidence: 99%
“…Having positive social relationships can promote healthier sleep by encouraging positive emotions, reducing stress, and preventing social isolation [ 9 ]. Social isolation can lead to greater stress and damage mental health [ 10 ]. Sufficient medical-social support may enable PLWHs to cope with the negative effects of stress more actively [ 6 ].…”
Section: Introductionmentioning
confidence: 99%